Effect of Germination and Fermentation of Pearl Millet on Proximate, Chemical and Sensory Properties of Instant "Fura"- A Nigerian Cereal Food - Inyang, C.U.; Zakari, U.M. (Pakistan Journal of Nutrition, 2007)
The study examined the effect of the germination and natural fermentation on the quality of instant "fura"-(a Nigerian cereal food). Pearl millet (Pennisetum glaucum) seeds were soaked for 12 h at room temperature (32±2°C) and sprouted for 48h at the same temperature. The sprouted seeds were washed, dried and milled into flour. The flour was divided into two portions, the first was allowed to ferment naturally at room temperature for 48h and used to produce germinated and fermented fura (GFF). The second portion was used for the production of Germinated Fura (GF). The cleaned, ungerminated grains were milled and the flour also divided into two portions. The first portion was wetted, fermented and used to produce Fermented Fura (FF). The second portion was used to produce Traditional Fura (TF). Standard assay procedures were used to evaluate the fura samples for nutrient composition and phytic acid levels. Germination and fermentation increased the protein, ash, crude fibre, phosphorus, calcium and iron levels of the fura samples. The phytic acid levels were significantly reduced (p<0.05) compared with the control (220 mg/100 for GFF, 230 mg 100g-1 for GF, 266 mg 100g-1 for FF and 416 mg 100g-1 for the control, TF. The sensory panelists rated the fura sample from germinated grains highly for all the sensory parameters investigated. Germination appeared to be a promising food processing method for improving the nutrient and energy densities of fura and when combined with fermentation, reduced phytic acid significantly (p<0.05).